Iringan Kuda Lumping Ngesti Budaya - SUBUH -; YUNI PRASETYO (Institut Seni Indonesia Yogyakarta, 2009)
Musical accompaniment of Ngesti Budaya horse dance. This article describes and analyzes a unique formperformance, presentation structure and growth of accompaniment of Ngesti Budaya horse dance through a descriptiveanalysis method. This dance represents a performing art owning characteristic, colour and also typical motion.One of the typical characteristic or element of this genre is a role of its musical accompaniment. Musical accompanimentalways accommodates dance movement pattern, assuring dance character, nguripke joget and develop;building dance plot atmosphere. At its growth, musical accompaniment does not only accompany dance, but withvarious its till can become important shares of dance and have to position is same in its presentation.